Survey the Infestation of Termite in Wheat in Semi-arid Region of Rajasthan: INFESTATION OF TERMITE IN WHEAT - Sanju, Sanju Piploda (Annals of Arid Zone, 2024)
A survey on termite infested wheat fields at seedling and maturity stages was carried out during rabi, 2021-22 and 2022-23 at different locations in five tehsils of Jaipur district. The average plant damage due to termite varied from 2.82 to 4.88% and 3.32 to 5.56% at seedling stage and 18.40 to 27.36% and 19.80 to 28.63% at crop maturity stage in 2021-22 and 2022-23, respectively. Maximum termite infestation damaging 4.88 and 5.56% (at seeding stage), 27.36 and 28.63% (at maturity stage) in wheat crop was recorded in Chomu tehsil during 2021-22 and 2022-23 respectively while the minimum damage was recorded in Dudu tehsil which ranged from 2.82 and 3.32% (at seedling stage) 18.40 and 19.80% (at crop maturity stage) during both years, respectively.